2021
DOI: 10.18632/aging.202558
|View full text |Cite
|
Sign up to set email alerts
|

ENAM gene associated with T classification and inhibits proliferation in renal clear cell carcinoma

Abstract: The potential involvement of T classification-related genes in renal clear cell carcinoma (ccRCC) must be further explored. Public data were obtained from The Cancer Genome Atlas (TCGA) database. An overall survival (OS) predictive model was developed and validated (TCGA train, 5 years, AUC = 0.73, 3 years, AUC = 0.73, 1 year, AUC = 0.76; TCGA test, 5 years, AUC = 0.74, 3 years, AUC = 0.65, 1 year, AUC = 0.73; TCGA all, 5 years, AUC = 0.72, 3 years, AUC = 0.71, 1 year, AUC = 0.75). Finally, ENAM was selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…6D). It has also recently been shown that ENAM can suppress cell proliferation in ccRCC and significantly increase cytotoxic cells, CD56 NK cells, NK cells, and CD8 + T cells in the immune TME 14 . In this work, a correlation was revealed between the hub genes of the ccRCC subtype with poor prognosis and the immune cell infiltration cells.…”
Section: Discussionmentioning
confidence: 94%
“…6D). It has also recently been shown that ENAM can suppress cell proliferation in ccRCC and significantly increase cytotoxic cells, CD56 NK cells, NK cells, and CD8 + T cells in the immune TME 14 . In this work, a correlation was revealed between the hub genes of the ccRCC subtype with poor prognosis and the immune cell infiltration cells.…”
Section: Discussionmentioning
confidence: 94%
“…With the arrival of the era of biological big data, the rapidly developing bioinformatics has greatly helped relevant researchers ( Yu et al, 2021b ; Ren et al, 2021 ). This study identified the potential role of PCDH7 in NSCLC through high-quality data analysis and validated it through further biological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…ENAM and WDR72 gene polymorphisms are associated with enamel development ( 35 , 36 ), and their mutations may lead to enamel hypoplasia ( 37 39 ). However, recent studies have found that the ENAM gene is associated with T classification and inhibits the proliferation of renal clear cell carcinoma ( 40 ) and that WDR72 genomic variants are associated with distal tubular acidosis and rapid declines in renal function ( 41 , 42 ). CLDN10 is a member of the tight junction protein claudin family, and abnormal CLDN10 expression may lead to tight junction dysfunction and thus affect tumor progression.…”
Section: Discussionmentioning
confidence: 99%